An evaluation of brigatinib as a promising treatment option for non-small cell lung cancer. (2nd September 2019) - Hamilton, G.; Hochmair, M.J.
ABSTRACT: Introduction : Brigatinib is a second-line inhibitor for the treatment of rearranged anaplastic lymphoma kinase (ALK) in lung cancer patients which has significant activity against brain metastases. This tyrosine kinase inhibitor (TKI) overcomes a wide range of ALK mutations which confer therapeutic resistance and is increasingly applied in first-line therapy due to improved benefit for patients compared to crizotinib, the current standard of care. Areas covered : The authors review the development and characteristics of brigatinib and discuss the optimal clinical use and sequence of the application of ALK inhibitors in patients progressing under therapy. Expert opinion : ALK-rearranged NSCLC can be treated with a broad range of approved and novel inhibitors at various stages of therapy, including the second-line therapeutic brigatinib. Besides this TKI, the second-line ALK inhibitors alectinib and ceritinib, as well as the third-line lorlatinib are approved for the treatment of ALK-positive NSCLC patients. The main challenge is to find sequences and combinations of ALK inhibitors which provide the best benefit for the patients.